Inhaling Difluoroethane Computer Cleaner Resulting in Acute Kidney Injury and Chronic Kidney Disease. (7th June 2018) - Calhoun, Kristen; Wattenbarger, Laura; Burns, Ethan; Hatcher, Courtney; Patel, Amol; Badam, Manjulatha; Khan, Abdul-Jabbar
Abstract : Difluoroethane is the active ingredient in various computer cleaners and is increasingly abused by teenagers due to its ease of access, quick onset of euphoric effects, and lack of detectability on current urine drug screens. The substance has detrimental effects on various organ systems; however, its effects on the kidneys remain largely unreported. The following case report adds new information to the developing topic of acute kidney injury in patients abusing difluoroethane inhalants. In addition, it is one of the first to show a possible relationship between prolonged difluoroethane abuse and the development of chronic kidney disease in the absence of other predisposing risk factors.